The inter-chamber differences in the contractile function between left and right atrial cardiomyocytes in atrial fibrillation in rats - Xenia Butova; Tatiana Myachina; Raisa Simonova; Anastasia Kochurova; Elena Mukhlynina; Elena Mukhlynina; Galina Kopylova; Daniil Shchepkin; Daniil Shchepkin; Anastasia Khokhlova; Anastasia Khokhlova (Frontiers in Cardiovascular Medicine, 2023)
IntroductionThe left and right atria (LA, RA) work under different mechanical and metabolic environments that may cause an intrinsic inter-chamber diversity in structure and functional properties between atrial cardiomyocytes (CM) in norm and provoke their different responsiveness to pathological conditions. In this study, we assessed a LA vs. RA difference in CM contractility in paroxysmal atrial fibrillation (AF) and underlying mechanisms.MethodsWe investigated the contractile function of single isolated CM from LA and RA using a 7-day acetylcholine (ACh)-CaCl2 AF model in rats. We compared auxotonic force, sarcomere length dynamics, cytosolic calcium ([Ca2+]i) transients, intracellular ROS and NO production in LA and RA CM, and analyzed the phosphorylation levels of contractile proteins and actin-myosin interaction using an in vitro motility assay.ResultsAF resulted in more prominent structural and functional changes in LA myocardium, reducing sarcomere shortening amplitude, and velocity of sarcomere relengthening in mechanically non-loaded LA CM, which was associated with the increased ROS production, decreased NO production, reduced myofibrillar content, and decreased phosphorylation of cardiac myosin binding protein C and troponin I. However, in mechanically loaded CM, AF depressed the auxotonic force amplitude and kinetics in RA CM, while force characteristics were preserved in LA CM.DiscussionThus, inter-atrial differences are increased in paroxysmal AF and affected by the mechanical load that may contribute to the maintenance and progression of AF.